History and philosophy of psychology - Chung, Man Cheung , 1962-; Hyland, Michael [ (Michael E.)] (John Wiley & Sons, 2012)
History and Philosophy of Psychology introduces students to the historical development of psychology and encourages them to explore the theoretical and philosophical implications. Distinct from other books on the history of psychology, the authors include ideas from both Eastern and Western philosophies